MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS DENGAN MENGGUNAKAN METODE VERBAL DAN NON VERBAL - Eliyati, Eliyati (LPPM STKIP PGRI Bandar Lampung, 2015)
Social studies designed to develop knowledge, understanding, and analytical skills of the social conditions in entering a dynamic social life. Social Science subjects are arranged in a systematic, comprehensive, and integrated in the learning process towards maturity and success in life in society. With this approach is expected to learners will gain a broader understanding and depth in the related fields of science.The purpose of this study increases student motivation in learning for learning can be understood heroism evenly. Improve the teaching and learning process in Subjects IPS. Increase students' understanding of the methods of reinforcement learning with verbal and non-verbal.The method used is a Classroom Action Research by using two cycles. While the research subject is class I. Data was collected with the scale of observation / observation and data analysis techniques performed by cycle analysis.Very significant changes between the results of the research cycle II, where the second cycle are the results of the evaluation can be considered good. Thus the study can already be said to be successful in the second cycle and no further cycle stages for the second cycle can already be categorized either by 91.67% on the evaluation of students with good results category and 8.33% of students with moderate category evaluation results. Thereby increasing student achievement be fine, although the classification was having similarities with the sense not decreased, but the author can give the conclusion that the achievement of students with good kategoro greatly increased with excellent classification. This study therefore has to be said berhasik the second cycle with the acquisition of 91.67% on average there is a category of students with good study results.